Analisis Kesesuaian Buku Ajar Matematika Kelas VIII SMP dengan Taksonomi TIMSS - Muawan, Mahya Munawaroh (2016)
This research was purposed to describe suitability of the math student's book 2013 curriculum junior high school of class VIII in 1st semester and 2nd semester with TIMSS taxonomy that correspond to the contain domain and cognitive domain. This research is a descriptive qualitative study. Descriptions of this research is done by giving an overview of the content and cognitive domains in TIMSS contained in each chapter in the book. Data collection method used by documentation, observation and interviews to obtain supporting data. The results of the analysis of the suitability of a book with cognitive domain of TIMSS. The math student's book 2013 curriculum junior high school of class VIII in 1st semester has the suitability of 21,49% for the cognitive domain of knowing, 35,24% for the cognitive domain of applying, 43,27% for the cognitive domain of reasoning and 2nd semester has suitability of 30,30% for the cognitive domain of knowing, 41,08% for the cognitive domain of applying 28,62% for the cognitive domain of reasoning